Histopathological and Immunohistochemical Evaluation of African Swine Fever Pigs in Bali Province - Septiani, Monica; Juniantito, Vetnizah; Priosoeryanto, Bambang Pontjo (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
African Swine Fever (ASF) is a disease affecting pigs, caused by a double-stranded DNA virus that is not transmissible to humans or other animals. It leads to significant economic losses due to high morbidity and mortality rates, particularly in densely populated pig regions like Bali Province. During the ASF outbreak from June to December 2023, this study conducted histopathological research on clinical samples. Biological materials from twelve pigs confirmed positive for ASF via qPCR examination were histopathologically analyzed. Tissue samples from various organs underwent processing and examination using hematoxylin and eosin staining. Immunohistochemistry (IHC) was employed to detect the ASF virus’s p54 protein. Clinical symptoms, anatomical pathology, and histological examination revealed characteristic acute ASF lesions. Immunohistochemistry consistently showed p54 viral antigen distribution in mononuclear cells/macrophages across various organs, with the spleen and lymph nodes being dominant sites in 12 pigs (100%). This comprehensive study demonstrates the effectiveness of IHC in detecting the ASF virus and characterizing its histopathology.Keywords: ASF; histopathology; immunohistochemistry